From concord to confession: the Wittenberg Concord and the Consensus Tigurinus in historical perspective. Issue 1 (2nd January 2016) - Burnett, Amy Nelson
Abstract : The differences between the Wittenberg Concord (1536) and the Consensus Tigurinus (1549) reflect a change in the function of a confession from an earlier, consensus-building model to a later concern with drawing boundaries and establishing confessional identity. The Wittenberg Concord used ambivalent language and strategic silence to define the boundaries of orthodoxy. Its acceptance by the south German churches did not mean either their full acceptance of Luther's position or the Wittenbergers' adoption of their position. The Swiss refusal to endorse the Wittenberg Concord confirmed Martin Luther's association of Zurich with heresy, and Jean Calvin's acceptance of it while in Strasbourg put him within the broad definition of evangelical orthodoxy that it set forth. In contrast, the Consensus Tigurinus contained terminology that made broad agreement with the Lutherans impossible. By moving Geneva out of fellowship with Wittenberg and into fellowship with Zurich, the Consensus Tigurinus created a Reformed Church able to stand against the Lutherans.